Asymmetric Cost Behavior In Indonesia - Muh. Pungki Nur Setiawan; Nur Aisyah Kustiani; Intan Dwi Puspitasari (Cakrawala Repositori IMWI, 2023)
Let’s say that last year’s sales had a 1% increase and expenses had a 0.53% increase compared to the year prior. If this year's sales decrease by 1%, how much will the expenses decrease? Most of us will answer that the expenses will decrease symmetrically, which is around 0.53%. However, this study finds that expenses increase by 0.53% per 1% increase in sales but only decrease by 0.39% per 1% decrease in sales. This phenomenon is called "asymmetric cost behavior" and occurred in the companies listed on the Indonesia Stock Exchange for the 2010–2017 period. This result fits with the study held by Anderson, Banker, and Jankiraman (2003), where they found that for a 1% increase in sales, the expense will increase by 0.55%, whereas it will only decrease by 0.35% when the sales decrease by 1%. Long-term assets, managerial decisions, and adjustment costs are the main factors behind this phenomenon.